Lebensqualität nach kolorektalen Operationen - Siassi, Ramin Michael; Weiss, Maren (Coloproctology, 2011)
Functional progress in colorectal surgery has shifted attention towards quality of life as a clinical endpoint. Quality of life is a complex, subjective construct. Variable factors such as pain and fatigue are often not diagnosed sufficiently although in many cases there are good treatment options. Static factors, e. g. origin or personality, exert a greater influence than generally assumed. Although these factors cannot be changed themselves, their assessment is important for the individual allocation of supportive and rehabilitative measures. Multidisciplinary management, including psycho-oncologic treatment, may therefore improve patients’ quality of life.